Cheat to win: How to hack tournament theory - Richard J. Arend (BRQ Business Research Quarterly, 2019)
It may be surprising that one of the most popular compensation schemes in business is so open to being hacked - to having managers cheat to win. We explore tournament theory to detail its vulnerabilities to various forms of cheating unilateral and multilateral. We identify who is most likely to be involved and under what conditions. We describe the costs to the victims, to the firm, and to society. We outline the possible strategic effects - in terms of firm performance. And, we discuss possible ways to address these vulnerabilities to the schemes we rely on to motivate managers to put in the right efforts, to take the right risks, and to lead the right way.
Keywords: M52; J33; D82; J31; D73; 650; Cheating; Managerial compensation schemes; Tournament theory; Vulnerabilities